Artificial Intelligence and Authorship - Del Federico, Caterina (The Matter of Intellectual Property: Studying the Economic, Political and Cultural Nodes of the Contemporary Media Industries. 15th Media Mutations International Conference, 2025)
This brief paper adopts a legal perspective and pursues the following aims: • to focus on the main legal sources in the field of copyright law; • to examine how these regulatory sources are inevitably connected to artificial intelligence, as well as to the new regulations on digital platforms and to the General Data Protection Regulation; • to identify the main legal challenges raised by these developments; • to put forward possible legal solutions. Innovations in artificial intelligence are raising several new questions about how copyright law principles will apply to content created or used by AI. Specifically, the reference is to the principles of: authorship, infringement and fair use. Indeed, the so-called generative AI computer programs recently developed are able to generate a wide variety of content (known as outputs) in response to a user’s textual prompts (known as inputs). Generative AI is able to achieve its results as these systems are fed with large amounts of data (‘data’ here has to be intended in a broad sense). The reference is, in particular, to existing works, such as writings, photos, paintings and other works of art. The legal issues of relevance are many. The first of them certainly concerns the profile of authorship: the question arises as to whether the artificial intelligence system can be considered the “author” of a work, with all that this entails legally speaking. Another troublesome issue relates to how such systems operate and – considering that they feed on data in a broad sense – there is the question of how their activities can comply with privacy legislation1 and especially copyright law. A further aspect certainly concerns the liability of platforms in cases of unlawful conduct involving the infringement of copyrighted works on the Internet2. The analysis of the issues mentioned above cannot be separated from the analysis of the relevant regulatory framework. In particular, it is appropriate to delve into the recent European Regulations. The reference is to: the General Data Protection Regulation Act, the Artificial Intelligence Act3 (last approved by the European Parliament), the Digital Services Act4 and the Digital Markets Acts5. Their impact on the Copyright Directive is crucial. An attempt will be made to elaborate on the issues mentioned, highlight the critical points arising in light of the relevant regulations and of the complex legal framework6, and provide some proposals for solutions.